2021
DOI: 10.1039/d0cs01165g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of Cr(vi) in water: lessons learned from fundamental studies and applications

Abstract: Converting toxic Cr(vi) to benign Cr(iii) would offer a solution to decontaminate drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 198 publications
1
84
0
Order By: Relevance
“…The results showed that the membrane surface electrical potential governed the overall efficiency of Cr 6+ removal. Because of surface passivation, the voltages applied to the EM for Cr 6+ reduction were higher than the theoretical value (Cr 3+ /Cr 6+ , 1.33 V vs. NHE); [161] as a result, 45% and 99% of Cr 6+ were removed by applying 3 and 7 V, respectively, implying that thorough Cr 6+ removal by EM is accomplished with increased overpotentials.…”
Section: Heavy Metal Detoxication By Electrified Membranes (Ems)mentioning
confidence: 84%
See 1 more Smart Citation
“…The results showed that the membrane surface electrical potential governed the overall efficiency of Cr 6+ removal. Because of surface passivation, the voltages applied to the EM for Cr 6+ reduction were higher than the theoretical value (Cr 3+ /Cr 6+ , 1.33 V vs. NHE); [161] as a result, 45% and 99% of Cr 6+ were removed by applying 3 and 7 V, respectively, implying that thorough Cr 6+ removal by EM is accomplished with increased overpotentials.…”
Section: Heavy Metal Detoxication By Electrified Membranes (Ems)mentioning
confidence: 84%
“…This not only aids in water recycling, but also increases the likelihood of value-added product recovery. FO has been shown in experiments to successfully remove a variety of contaminants such as nitrates, sulphates, and phosphates, hardness, high levels of suspended solids, CODs, and heavy metals from industrial effluents [128,161,185]. The draw solution-induced dewatering operating principle makes it a broad-spectrum, robust option for treating such complex streams.…”
Section: Forward Osmosis (Fo)mentioning
confidence: 99%
“…Studies with higher concentrations of Cr(VI) showed a higher stability of Cr 2 O 7 2− which improved with higher ionic strength [63]. Thus, it is described that for 50 mM Cr(VI) in 3 M KCl, the predominant species is Cr 2 O 7 2− in acid medium (pH 0.75-6.45) and HCr 2 O 7 − at lower pH values [62]. By last, CrO 4 2− is the predominant species at neutral to basic pH regardless of the concentration.…”
Section: Speciation Of Cr(vi)mentioning
confidence: 95%
“…where the pKa1 value is lower than 1.5 and the pKa2 ranges from 5.76 to 7 in the temperature range of 20-25 °C (according to the experimental conditions used in this paper). The predominant species are HCrO 4 − at acid conditions (pH 0.75-6.45) and H 2 CrO 4 at highly acid conditions (pH < 0.75) [61,62]. When the concentration of Cr(VI) increases, the chromate/dichromate equilibrium occurs:…”
Section: Speciation Of Cr(vi)mentioning
confidence: 99%
“…Water contamination from chromium and dye has been widely remediated over the past years. In this context, Cr (VI) and MO have been efficiently removed using various techniques including adsorption, electrochemical methods, reduction, biological remediation, ion exchange, and chemical precipitation [12][13][14][15]. Due to its low cost, great efficiency, and simple processing procedures, adsorption is considered the most promising method.…”
Section: Introductionmentioning
confidence: 99%